Prenatal Care and Subsequent Birth Intervals - Teitler, Julien O. (2012)
CONTEXT: Research on the effectiveness of prenatal care has focused primarily on birth outcomes, finding small effects at the population level. However, prenatal care generally includes postpartum contraceptive and health education that may enable women to better control their subsequent fertility. Associations between prenatal care and subsequent fertility have not been previously explored. METHODS: Using longitudinally-linked birth records from New Jersey between 1996 and 2006, we estimated multinomial logistic regression models to investigate associations between prenatal care (timing or adequacy) in a mother’s first birth and timing of her second birth, controlling for sociodemographic characteristics and hospital and year of birth. RESULTS: Most mothers initiated prenatal care in the first (85%) or second (12%) trimester. Initiation of care after the first trimester is strongly associated with short subsequent birth intervals. The odds of having a second child in fewer than 18 months (compared to 18–59 months) were 19% higher if the mother initiated care in the second versus the first trimester, 26% higher if she initiated care in the third trimester, and 61% higher if she did not receive any care, all else equal. The associations are robust to alternative measures of prenatal care and birth intervals and are stronger for mothers with low levels of education. CONCLUSIONS: The findings suggest that prenatal providers should capitalize on their limited encounters with mothers who initiate prenatal care late or use it sporadically to make information about family planning available. This issue is timely given recent and proposed budget cuts to public family planning.